2012
DOI: 10.1128/cvi.05615-11
|View full text |Cite
|
Sign up to set email alerts
|

Memory B Cell and Other Immune Responses in Children Receiving Two Doses of an Oral Killed Cholera Vaccine Compared to Responses following Natural Cholera Infection in Bangladesh

Abstract: ABSTRACTCurrent oral cholera vaccines induce lower protective efficacy and shorter duration of protection against cholera than wild-type infection provides, and this difference is most pronounced in young children. Despite this, there are limited data comparing immune responses in children following wild-type disease versus vaccination, especially with regard to memory responses associated with long-term immunity. Here, we report a comparison of immune responses in young childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 40 publications
2
57
1
Order By: Relevance
“…We have recently demonstrated that LPSspecific antibody and memory B cell responses are correlated with protection against cholera in household contacts of patients with cholera (14). We have also shown that in children, two doses of WC-rBS vaccine induce significantly lower plasma LPS antibody levels and memory B cell levels than wild-type infection (15). Thus, we hypothesized that differences in V. cholerae polysaccharide-specific humoral responses partly account for differences in the durations of protection provided by infection and vaccination.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…We have recently demonstrated that LPSspecific antibody and memory B cell responses are correlated with protection against cholera in household contacts of patients with cholera (14). We have also shown that in children, two doses of WC-rBS vaccine induce significantly lower plasma LPS antibody levels and memory B cell levels than wild-type infection (15). Thus, we hypothesized that differences in V. cholerae polysaccharide-specific humoral responses partly account for differences in the durations of protection provided by infection and vaccination.…”
mentioning
confidence: 72%
“…The mechanisms behind these observations are not well understood. We have previously shown that immune responses, including memory B cell responses, to V. cholerae LPS are associated with immunity against cholera (14,27) and that in children memory B cell responses targeting LPS are induced and more sustained by natural infection than by vaccination (15). In this report, we describe the antibody response of child vaccinees and patients against OSP, the component of LPS that defines serogroup specificity and perhaps is an important target of immune responses that mediate protection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The mechanism underlying the longer protection afforded by natural infection with cholera is not yet fully understood, although memory responses particularly to LPS may play a part (14,18,20,33). Interestingly, current oral killed-cholera vaccines do not induce memory B-cell responses targeting LPS, while wild-type disease does, even in young children (1,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…46 Serum vibriocidal activity, measured by a bactericidal assay requiring the fixation of complement by antibody that is bound specifically to vibrios, is used extensively as a marker of immunity to V. cholerae, but has limitations. 47,48 On the basis of Genomics of response to cholera vaccine PP Majumder et al recent reccommendations 49 to measure LPS-response in multiple immunoglobulin isotypes and results 50,51 which indicate that levels of all immunoglobulin isotypes (IgG, IgM and IgA) determine the nature and extent of protection afforded by oral cholera vaccination, we have used the total anti-LPS AR and also the traditional vibriocidal assay. Clinical trials of many oral vaccines have underscored the importance of understanding the reasons for variability in immune response to oral vaccines, 52 and the identification of genetic factors in the host linked to vaccine immunogenicity.…”
Section: Discussionmentioning
confidence: 99%